Determining the Essence of the Labor Potential Components for Enhancing the Effectiveness of Business Management - I. RAIKOVSKA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
The article’s objective is to outline the essence labor potential and its components in the business management system. The objective is achieved through investigating the structure and content of the labor potential as part of the business management system, with determining change in its semantic content.An extensive review of economic literature is made. It shows that the labor potential can be interpreted as (i) the integral measure of quantitative and qualitative parameters of the economically active population, which, being subjected to the operations of formation, transformation, relocation and realization, carry out physical, career, professional and qualification transfer in the spatial and temporal interval; (ii) the totality of able-bodied population whose intellectual development, competencies, abilities, experiences, moral values, customs, traditions, ideologies and patriotism create a source of the business competitive advantage. It is proposed that labor potential should be created by components such as health, culture and education of personnel, which is a necessary condition in complex business management; the essence of each structural component that has critical importance for the enterprise performance and macroeconomic growth is revealed.   In accordance with the modern understanding of labor potential, the role of the labor potential is highlighted at not only at individual, but at business enterprise level at which the labor potential can be interpreted as the totality of qualifications and professional skills of all the business enterprise employees and their achievements in effective organization of labor and development of personnel.